Teacher Professionalism in Facing the Challenges of Digitization of Learning - Eka Sriwahyuni (CV. Get Press Indonesia, 2025)
The development of digital technology brings significant changes in the world of Education, demanding teachers to adapt quickly to various forms of digitization of learning. Teacher professionalism is a key factor in addressing this challenge, encompassing pedagogical competence, technology, and work ethics. Purpose: this study aims to analyze how teachers in Padang demonstrate professionalism in facing the challenges of digitizing learning and identify supporting and inhibiting factors. Methods: the method used is a qualitative case study in one of the public junior high schools in Padang. Data collection techniques include observation, in-depth interviews, and documentation studies. Results: the results showed that most teachers are trying to adjust to the demands of digitization through online training, the use of digital learning platforms, as well as the development of interactive teaching media. However, the challenges faced include limited ICT facilities, differences in the level of digital literacy among teachers, as well as internet network constraints in some regions. Implications: this study implies the need for stronger institutional support, both from local governments and education units, to sustainably strengthen the professional capacity of teachers. Conclusion: teacher professionalism in the digital age is determined not only by mastery of technology, but also by commitment to continuous learning and adaptability. The development of digital competencies and the creation of an inclusive learning ecosystem are key factors in effectively addressing the challenges of digitalization.